RELEVANSI KONSEP JINAYAH TERHADAP PENCEGAHAN KORUPSI DAN PENYALAHGUNAAN WEWENANG DALAM MSDM - Harahap, Mufti Fahrizal; Lubis, Muhlisah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Corruption and abuse of authority are serious problems in various sectors, including in Human Resources Management (HRM). Unethical actions such as bribery, nepotism and data manipulation can damage the integrity of an organization and reduce public trust in the institution. This article examines the relevance of the concept of jinayah in Islamic law to preventing corruption and abuse of authority in HRM. The concept of jinayah, which includes criminal acts that harm society, teaches basic principles such as justice ('adl), trust (honesty), and accountability (mas'uliyyah). The application of these principles in HRM can prevent corrupt practices and abuse of authority by enforcing appropriate morals and laws. Through an approach based on Islamic ethics, this article shows how fair, transparent and responsible human resource management can be established by utilizing the concept of jinayah as a guide. In this context, preventing corruption and abuse of authority does not only require a legal approach, but also a moral approach that is able to uphold justice and integrity in the organization.